PEMANFAATAN NODE MCU ESP8266 SEBAGAI KOMUNIKASI PENGAKSESAN DATA WEB SERVER PADA STUDI KASUS SISTEM PENGAMANAN PINTU LEMARI ARSIP BERBASIS QRCODE - BUSRAN; Satria Yaumil (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2022)
People's need for electrical energy is getting bigger along with the development of technology and population. To meet this increasing demand, it is necessary to develop energy resources. Solar energy is an effective sustainable natural resource, because of its existence, availability, and sustainability, which are adequate and free from pollution. Solar energy can be used to produce electrical energy by using solar panels. The use of solar panels as a necessity for electric current has been widely applied, but of course there is still a static position that makes solar panels ineffective in getting sunlight which will be converted into electric current used. The purpose of this study is to make a solar panel controller that can move in the direction of the sun's position with a time-based method, so that the position of the solar panel is always facing the sun even though the sun's position is covered by clouds or obstacles, which makes solar panels store more solar energy as a source of energy. community needs in using electrical energy. The solar panel is connected by using a screw iron that uses a nut to connect it to the stepper motor, then the movement of this stepper motor will be controlled every 20 minutes using the A4988 Stepper Motor Driver, in addition to the rotation of the motor as a driving force for the direction of the solar panel..